The impact of financial technology on consumption function of the theory of absolute income hypothesis: a partial adjustment model approach (the Indonesian evidence) - Saraswati, Birgitta Dian; Maski, Ghozali; Kaluge, David; Sakti, Rachmad Kresna (Business: Theory and Practice, 2022)
Households are economic actors that play a significant role in the economic condition. Thus, households’ consumption expenditures are a variable that deserves a through analysis in an economy. This study aims to identify the impact of financial technology on household consumption by using the theory of the absolute income hypothesis. We use the partial adjustment model (PAM) approach and the Chow test to detect the structural change on households’ consumption function in Indonesia with the observation period of 1990–2017. The results demonstrate that Indonesian households’consumption function exhibits structural change because of the development of financial technology 3.0 era that started in 2000. Besides, the partial adjustment model also suggests that financial technology positively affects Indonesian households’consumption in both short-run and long-run. The findings imply that on the one hand, the findings are a positive signal to rely on finteh as the factor that encourages economic growth in Indonesia. On the other hand, the results indicate that fintech motivates the public to be more consumptive that will potentially lead to higher inflation rates.